Refugee Resettlement as an Alternative to Asylum. (12th March 2018) - Hashimoto, Naoko
ABSTRACT: Despite the importance of refugee resettlement being frequently emphasised, there is only a limited amount of empirical research on why an increasing number and variety of States admit refugees through resettlement, when it is not an obligation under international law. This article first sets out the four traditional perspectives on States' motives for resettlement, based on well-established theories of International Relations, namely egoistic self-interest, altruistic humanitarianism, reciprocity, and international reputation. After examining the applicability of each of the traditional perspectives in light of past and recent resettlement practice in a deductive manner, the article puts forward a different hypothesis: that States perceive resettlement as an alternative to asylum in terms of migration management, given the recent empirical and discursive trend. While the article by no means suggests that such a perception is a justifiable explanation for States' motives for resettlement, the perception seems to add a different and relevant hypothesis when tracing the logic behind States' increasing interest in resettlement.